Excess thermal resistivity in N2–CO solid solution at low carbon monoxide concentration: Physics in Quantum Crystals - Stachowiak, P.; Sumarokov, V.V.; Mucha, J.; Jeżowski, A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
The results of measurements of the thermal conductivity of pure and carbon-monoxide-doped nitrogen crystals, for samples containing up to 0.7% of CO molecules, in the temperature range1.2–26 K are presented. From the preliminary analysis it results that the interaction of phonons with admixture molecule featuring the same mass, as the host molecule, is relatively weak and depends weakly on the admixture concentration within investigated range of carbon monoxide in nitrogen crystal.